Book Reviews. Issue 3 (1st October 2016) - Anders, Ellen; Brewster, Maureen; Hart, Rachel; McKnight, Alanna; Moir, Aidan; Snelgrove, Laura; Sperling, Joy
MOROCCAN FASHION: DESIGN CULTURE AND TRADITION, M. ANGELA JANSEN (2015) London: Bloomsbury Publishing, 144 pp., ISBN: 9781472524677, h/bk, 89.79INDIAN FASHION: TRADITION, INNOVATION, STYLE, ARTI SANDHU (2015) 1st ed., London, New Delhi, New York and Sydney: Bloomsbury Academic, 216 pp., ISBN: 9781847887795, p/bk, 29.95DRESS AND IDEOLOGY, SHOSHANA-ROSE MARZEL AND GUY D. STIEBEL (2015) London and New York: Bloomsbury Academic, 248 pp., ISBN: HB-9781472525499, p/bk, 27.99FASHION WRITING AND CRITICISM: HISTORY, THEORY, PRACTICE, PETER MCNEIL AND SANDA MILLER (2014) London and New York: Bloomsbury, 151 pp., ISBN: 9870857854469, £19.99DIANA AND BEYOND: WHITE FEMININITY, NATIONAL IDENTITY, AND CONTEMPORARY MEDIA CULTURE, RAKA SHOME (2014) Urbana, Chicago and Springfield: University of Illinois Press, 272 pp., ISBN: 9780252038730, cloth, 95; ISBN: 9780252080302, p/bk, 30; ISBN: 9780252096686, e-bookCOOL SHADES: THE HISTORY AND MEANING OF SUNGLASSES, VANESSA BROWN (2015) London and New York: Bloomsbury Academic, 177 pp., ISBN: 9780857854445, p/bk, £19.99AFRICA IN THE AMERICAN IMAGINATION: POPULAR CULTURE, RACIALIZED IDENTITIES, AND AFRICAN VISUAL CULTURE, CAROL MAGEE (2012, 2014) Jackson, Mississippi: University Press of Mississippi, 263 pp., ISBN 978-1-617703-152-6 (h/bk), ISBN 978-1- 61703-153-3 (ebook), 55.00